Analysis of a turbulent wind field in a street canyon: Good agreement between LES model results and data from a mobile platform - Bastian Paas (Meteorologische Zeitschrift, 2021)
Urban wind fields are of concern because the near-ground wind vector drives the ventilation of cities, which involves, among other things, the translocation and dilution of air pollutants. To study flow patterns in the urban atmospheric boundary layer, turbulence-resolving tools are needed since numerous roughness elements are present that cause the flow to be of highly turbulent nature. Therefore, we developed a mobile, fast-response measurement platform that is situated on a cargo bicycle. This mobile platform was deployed in a case study collecting data at street level within a complex, urban area that includes street canyons, open squares, street intersections as well as courtyard entrances. Results were compared to numerical large eddy simulation (LES) data from the model PALM. Outcomes of both methods were qualitatively analyzed; results show that both methods were able to identify complex flow patterns, including small-scale structures such as jetting flows, vortices, recirculation areas, and a convergence zone where air masses collide. Results of both methods generally matched well, even for areas that featured highly complex, three-dimensional flow structures. We conclude that both the model PALM and the mobile platform are valuable tools for gathering insights about complex flow structures in real-world environments.